Fecal microbiota transplantation inhibits colorectal cancer progression: Reversing intestinal microbial dysbiosis to enhance anti-cancer immune responses - Yu, Hao; Li, Xing-Xiu; Han, Xing; Chen, Bin-Xin; Zhang, Xing-Hua; Gao, Shan; Xu, Dan-Qi; Wang, Yao; Gao, Zhan-Kui; Yu, Lei; Zhu, Song-Ling; Yao, Li-Chen; et al. (Frontiers in Microbiology, 2023)
Many lines of evidence demonstrate the associations of colorectal cancer (CRC) with intestinal microbial dysbiosis. Recent reports have suggested that maintaining the homeostasis of microbiota and host might be beneficial to CRC patients, but the underlying mechanisms remain unclear. In this study, we established a CRC mouse model of microbial dysbiosis and evaluated the effects of fecal microbiota transplantation (FMT) on CRC progression. Azomethane and dextran sodium sulfate were used to induce CRC and microbial dysbiosis in mice. Intestinal microbes from healthy mice was transferred to CRC mice by enema. The vastly disordered gut microbiota of CRC mice was largely reversed by FMT. Intestinal microbiota from normal mice effectively suppressed cancer progression as assessed by measuring the diameter and number of cancerous foci and significantly prolonged survival of the CRC mice. In the intestine of mice that had received FMT, there were massive infiltration of immune cells, including CD8+ T and CD49b+ NK, which is able to directly kill cancer cells. Moreover, the accumulation of immunosuppressive cells, Foxp3+ Treg cells, seen in the CRC mice was much reduced after FMT. Additionally, FMT regulated the expression of inflammatory cytokines in CRC mice, including down-regulation of IL1a, IL6, IL12a, IL12b, IL17a, and elevation of IL10. These cytokines were positively correlated with Azospirillum_sp._47_25, Clostridium_sensu_stricto_1, the E. coli complex, Akkermansia, Turicibacter, and negatively correlated with Muribaculum, Anaeroplasma, Candidatus_Arthromitus and Candidatus Saccharimonas. Furthermore, the repressed expression of TGFb, STAT3 and elevated expression of TNFa, IFNg, CXCR4 together promoted the anti-cancer efficacy. Their expressions were positively correlated with Odoribacter, Lachnospiraceae-UCG-006, Desulfovibrio, and negatively correlated with Alloprevotella, Ruminococcaceae UCG-014, Ruminiclostridium, Prevotellaceae UCG-001 and Oscillibacter. Our studies indicate that FMT inhibits the development of CRC by reversing gut microbial disorder, ameliorating excessive intestinal inflammation and cooperating with anti-cancer immune responses.